Effectiveness Of Perineum Massage In Primigravida Pregnant Women On Perineum Rupture In Materials - Khusnul Nikmah; Rizki Amalia; Ayu Erisnawati (Universitas Nahdlatul Ulama Surabaya, 2022)
Infection is one of the important causes of maternal mortality and morbidity. One of the risk factors for puerperal infection is due to actions during delivery such as episiotomy and perineal rupture. The perineum is the most common site for rupture during labor. Perineal rupture occurs in 85% of women during birth and 60-70% requires suturing. Perineal rupture occurs in almost all first deliveries. For this reason, efforts are needed to prevent perineal rupture, one of which is a simple method that everyone can do by doing perineal massage. Objective: To determine the effectiveness of perineal massage in women giving birth with perineal rupture at BPM Kusmawati, Amd Keb Surabaya. Methods: The design used is a quasi-experimental design with a Static Group Comparison. The study was conducted at BPM Kusmawati, Amd Keb Surabaya on September 5 to November 5, 2021. The population of all primigravida mothers at 37 - 40 weeks of gestation was 40 people. The sampling technique used Total Sampling which was divided into 20 subjects in the intervention group and 20 in the control group. Data collection techniques using a checklist sheet. The data were analyzed using the Fisher Exact Test. Results: showed p value = 0.000 (<0.05), then perineal massage was effective in preventing perineal lacerations and episiotomy in normal delivery, so perineal massage could be applied especially to primigravida from 37 - 40 weeks of gestation to prevent spontaneous perineal rupture. in normal delivery in women giving birth at BPM Kusmawati, Amd Keb Surabaya.